Editorial - Vallejos Vásquez, Sheily (2015)
A new issue of the Journal of the Library School of Library, Documentation and Information of the National University for the second half of 2015. In this five articles on different topics presented include: 2.0 users, we manage information, catalogs or OPAC's, sources of information and archival Costa Rican identity.